Чистая душа: роман : пер. с татар. / Мирсай Амир - Амир Мирсай (Татарское книжное издательство, 1981)
Экземпляры: (20180418) / Инвентарный номер: 1241 / Цена: 1.90 / Авт.знак: А 62 / ББК: 84(2Рос=Тат)